Phenotyping of a new yeast mapping population reveals differences in the activation of the TORC1 signalling pathway between wild and domesticated yeast strains - Guilherme Rocha; Melissa Gómez; Camila Baeza; Francisco Salinas; Claudio Martínez; Eduardo I. Kessi-Pérez (Biological Research)
Abstract Domestication can be understood as a symbiotic relationship that benefits both domesticator and domesticated species, involving multiple genetic changes that configure the phenotype of the domesticated species. One of the most important domesticated species is the yeast Saccharomyces cerevisiae, with both domesticated strains used for different fermentations processes for thousands of years and wild strains existing only in environments without human intervention; however, little is known about the phenotypic effects associated with its domestication. In the present work, we studied the effect of domestication on yeast TORC1 activation, a pleiotropic signalling pathway conserved across the eukaryotic domain. To achieve this goal, we improved a previously generated methodology to assess TORC1 activation, which turned out to be as effective as the original one but also presents several practical advantages for its application (such as facilitating confirmation of transformants and putting the Luc reporter gene under the control of the same P RPL26A promoter for each transformed strain). We then generated a mapping population, the so-called TOMAN-G population, derived from the “1002 Yeast Genomes Project” population, the most comprehensive catalogue of the genetic variation in yeasts. Finally, strains belonging to the TOMAN-G population were phenotyped for TORC1 activation, and then we compared the results obtained between yeast strains with different ecological origins, finding differences in TORC1 activation between wild and domesticated strains, particularly wine strains. These results are indicative of the effect of domestication on TORC1 activation, specifically that the different evolutionary trajectories of wild and domesticated strains have in fact caused differences in the activation of this pathway; furthermore, the phenotypic data obtained in this work could be used to continue underlying the genetic bases of TORC1 activation, a process that is still not fully understood, using techniques such as GWAS to search for specific genetic variants underlying the observed phenotypic variability and phylogenetic tree inferences to gain insight into the evolutionary relationships between these genetic variants.